The Impact of organizational culture in promoting the elements of the Six S: Analytical study of the opinions of a selected sample of employees of Al-Khansa Teaching Hospital in Mosul - Jasim Mohammed, Sanaa; Salem Khalil, Shahla; Abdul Sattar Talbi, Ahmed; Mahmood Edham, Shahla (Iraqi Journal for Administrative Sciences, 2024)
يThe research aims to determine the impact of organizational culture in enhancing the elements of (6S) in the organization, and by searching for the problem through the question that does the organizational culture contribute to strengthening the (6S) methodology in the researched organization, centering on whether there is an effect of organizational culture in promoting the elements of the six years (6S), and in light of this, the hypothesis scheme for the research was constructed and the research hypotheses emerged from it, and to test the validity of the hypotheses, data were collected through the questionnaire tool and prepared for this purpose, as a random sample was selected from the group of workers in various specialties in the hospital, which amounted to (50) Affiliated with the various departments of Al-Khansa Teaching Hospital in Mosul to be a sample for research, and the research reached a set of conclusions and recommendations.